Evaluation of Acoustic Features after Refurbishment Works Inside Two Historical Opera Theatres Located in Italy - Antonella Bevilacqua (Acoustics, 2021)
The acoustical characteristics of a room where the artistic performance is presented to the audience have a critical impact on the experience of both artists and spectators. It is important to know how the original aspects and the refurbishment works throughout the centuries are brought to the characterization of the sound field in such theatres, with positive and negative consequences. This paper presents the acoustical assessment of the Teatro Nuovo of Spoleto and the Teatro Alighieri of Ravenna, very important landmark centers for their historical and cultural activities. The acoustical characteristics have been gathered by placing the sound source on both the stage and orchestra pit, and the receivers in the stalls and balconies areas at different levels. It is of great interest to show the acoustical parameters of such Opera houses and some acoustical limits derived from intermediate interventions due to the need of the committees to allocate as many spectators as possible for income reasons. After an acoustic analysis of the existing conditions, the authors compare the acoustic behaviour inside the Teatro Nuovo of Spoleto using the image-source method (ISM) to investigate a change of ceiling configurations that occurred with the refurbishing works of the 20th century.